2017
DOI: 10.1002/mnfr.201700031
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects against atherosclerosis by inhibiting dendritic cell activation

Abstract: Our data indicate that quercetin attenuates atherosclerosis progression by regulating DC activation via Dab2 protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Single target cure is not enough. Phytomedicine, such as Quercetin (Lin, Wang, Wang, & Ling, 2017), has drawn much attention. TASAES, isolated from Aralia elata (Miq) Seem, which is widely used in eastern Asia and Russia.…”
Section: Discussionmentioning
confidence: 99%
“…Single target cure is not enough. Phytomedicine, such as Quercetin (Lin, Wang, Wang, & Ling, 2017), has drawn much attention. TASAES, isolated from Aralia elata (Miq) Seem, which is widely used in eastern Asia and Russia.…”
Section: Discussionmentioning
confidence: 99%
“…Q3G concentrations were based on previous investigations (e.g., ref. [] and []) showing them to be efficacious at reducing dyslipidemia and dysglycemia in mice fed a high‐fat diet (HFD). The mice were kept under these diets for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…That effect is mainly related to the ability of quercetin in reducing recruitment of neutrophils (myeloperoxidase [MPO] activity [33,69,72]), oxidative stress [33,54,69,73,74], COX-2 in the knee joint (arthritis model) [33], NLRP3 inflammasome activation (inhibition of ASC speck formation and ASC oligomerization) in macrophages [57], p65 NF-κB activation [53,54] and MAP kinases signaling in macrophages [53], p50 NF-κB activation in primary human keratinocytes [55], and TNF-α, IL-1β and IL-6 production in RAW 264.7 cells stimulated by LPS [75]. Recent studies demonstrated that quercetin is able to modulate the neutrophils actin polymerization [76], pro-inflammatory cytokines expression by mast cells [77,78] and monocytes [79,80], dendritic cell activation [81] and maturation [82], and the phenotype M1 to M2 in macrophages [83][84][85][86]. In the past few years, increasing attention has been paid to the analgesic effect of quercetin [33,54,71,73,74,87].…”
Section: Flavonolsmentioning
confidence: 99%